Miscellanea on Encephalopathies A Second Look - Tanasescu, Radu (IntechOpen, 2012)
The book project "Miscellanea on Encephalopathies-a second look" aims to cover some of the important aspects regarding metabolic, hypoxic, neoplasm- and drug-related encephalopathies, by transmitting valuable information filtered through the real life clinical and research experience of the authors.